2015
DOI: 10.1111/ddi.12373
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of species richness and functional diversity in Costa Rican terrestrial mammals: implications for conservation

Abstract: Aim Functional diversity is a relatively recent approach to quantify species diversity and may provide a better understanding of the linkages between biological diversity and ecosystem functioning. Understanding the relationships between mammal species richness and functional diversity, the factors that influence these relationships, and the spatial scale at which they operate, can improve our knowledge of ecosystem functioning and may benefit conservation planning.Methods We evaluated spatial patterns of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 75 publications
(164 reference statements)
5
47
2
3
Order By: Relevance
“…Previous studies of global and regional variation on FD in mammals and other groups have shown similar patterns than those obtained here [3, 4, 37, 68, 69], and most studies have identified anthropogenic intervention–in terms of land-cover transformation, as a major driver for FD loss [14, 15, 38, 70]. However, very few studies have assessed the influence of species at risk and the potential functional loss due to species extinctions [38, 50, 71].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies of global and regional variation on FD in mammals and other groups have shown similar patterns than those obtained here [3, 4, 37, 68, 69], and most studies have identified anthropogenic intervention–in terms of land-cover transformation, as a major driver for FD loss [14, 15, 38, 70]. However, very few studies have assessed the influence of species at risk and the potential functional loss due to species extinctions [38, 50, 71].…”
Section: Discussionsupporting
confidence: 88%
“…Further explorations into mammal FD at finer and more detailed resolutions and more precise definitions of human intervention would likely provide confirmation of our results and will increase the precision of the trends found in our results [3, 4]. Our definition of FD, as linked to the concept of functional richness, is the functional trait space occupied by species within a community [75], influencing productivity and in turn functionality and resilience at ecosystem and community scale.…”
Section: Discussionsupporting
confidence: 55%
“…All else being equal, the probability of an assemblage including species with unique trait compositions increases with the number of species (e.g., Naeem, Bunker, Hector, Loreau, & Perrings, ). Indeed, most, if not all, studies that have examined the relationship between functional richness and species richness, found a positive saturating association (e.g., Petchey, Evans, Fishburn, & Gaston, ; Farias & Svensson, ; González‐Maya, Víquez‐R, Arias‐Alzate, Belant, & Ceballos, ). This relationship is not necessarily linear, due to a decrease in the appearance of new traits as the number of species increases (e.g., Farias & Svensson, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to evidence from some recent studies, taxonomic, functional, and phylogenetic diversity should respond to distinct ecological drivers, implying that different facets of diversity may be complementary and provide integrative information about community assembly (González‐Maya, Víquez‐R, Arias‐Alzate, Belant, & Ceballos, ; Heino & Tolonen, ; Saito, Siqueira, et al, ). Generally, taxonomic diversity might be affected by both deterministic (e.g., environmental conditions) and some stochastic processes (e.g., dispersal and ecological drift) (Munemitsu & Noriko, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to evidence from some recent studies, taxonomic, functional, and phylogenetic diversity should respond to distinct ecological drivers, implying that different facets of diversity may be complementary and provide integrative information about community assembly (González-Maya, Víquez-R, Arias-Alzate, Belant, & Ceballos, 2016;Heino & Tolonen, 2017b;.…”
Section: Introductionmentioning
confidence: 99%